Third Annual Short Course in Educational Leadership : Littledale Conference Centre, St. John's, Newfoundland, February 12-17, 1989. Day 4. Plenary session 2. Tape 1 of 2 - Memorial University of Newfoundland. Extension Service (MUN Extension Service, 1989)
Dr. M. Mulcahy examines the moral dilemma in which school administrators operate. She suggests some principles for them to use as a guide. She gives some attention to the issue of moral education and whether it should be linked to Christian faith or a secular moral code.